Performance Management System for Information Technology Project (Case Study: NEW ROAM SR Project in Coca-Cola Amatil Indonesia) - Wisaksono, Mohammad; Wibisono, Dermawan (The Indonesian Journal of Business Administration, 2013)
Information Technology is playing a big role integrating information flow. Information technology implementation is an investment with targeted to gain the efficiency of competitive edge over competitor for business. Ensuring the investment made in Information Technology project to reach the objective and provides value for the business is something that people are used to rely on triple constraint on time, on scope and on budget. Triple constraint only evaluate project fulfillment based on the project plan, on time, on scope and on budget but does not guarantee the final output is providing expected value for business, triple constraint is considered as short term goal which is easy to use for evaluating project but do not reflect the actual impact and benefit. A case study conducted in Coca-Cola Amatil Indonesia to design a performance management system to provide a comprehensive IT project key performance indicator based on PRISM approach to ensure all necessary strategy, process and capability in place to achieve project stakeholder satisfaction and contribution.Â Keywords: Analytical Hierarchy Process, PRISM, Information Technology Project